Understanding the challenges in sustaining the bills of quantities in Malaysia - Bandi, Shamsul Hadi; Abdullah, Fadhlin (2012)
Reviews of the past and current literatures have indicated differing views and opinions on the future outlook of the Bills of Quantities (BQ). Numerous issues have been identified from the literatures and until a viable solution is identified, current issues will likely limit its potential as a source of information in construction project. Based on the identified issues, this paper aim to identify issues relating to the usage and application of BQ in the construction industry by critically reviewing and appraise the existing literatures. The study has employed an extensive literature reviews which extensively synthesized findings, suggestions and comment of previous research works in order to identify key points imperative to strategize future research work. As a result, 13 general issues and 17 specific issues pertaining to the application of the BQ in the construction industry have been outlined which are applicable in Malaysia and elsewhere. At the end of the paper, a list of challenges confronting the BQ is presented as a basis for further improvement and starting point for future research work to be carried out.